Effective Safety Management in Construction Project - Othman, I. (Institute of Physics Publishing, 2018)
Effective safety management is one of the serious problems in the construction industry worldwide, especially in large-scale construction projects. There have been significant reductions in the number and the rate of injury over the last 20 years. Nevertheless, construction remains as one of the high risk industry. The purpose of this study is to examine safety management in the Malaysian construction industry, as well as to highlight the importance of construction safety management. The industry has contributed significantly to the economic growth of the country. However, when construction safety management is not implemented systematically, accidents will happen and this can affect the economic growth of the country. This study put the safety management in construction project as one of the important elements to project performance and success. The study emphasize on awareness and the factors that lead to the safety cases in construction project. Â© Published under licence by IOP Publishing Ltd.